School leader internship developing, monitoring, and evaluating your leadership experience - Martin, Gary E., 1949 July 16-; Danzig, Arnold Bob, 1948-; Flanary, Richard A.; Orr, Margaret Terry, 1953- (Routledge, Taylor & Francis Group, 2022)
"School Leader Internship 5th Edition challenges aspiring educational leaders and interns to better assess, prepare, plan, implement, and evaluate their internship experience in preparation for certification, licensure, and advancement into school building-level leadership positions. In this updated edition, the content is organized around the latest National Education Leadership Preparation (NELP) Standards and includes intern activities that develop skills in essential areas including ethics, equity and cultural responsiveness, curriculum development, community of care, support of teachers and staff, school partnerships, and continuous school improvement. This unique book provides step-by-step guidance for interns, their supervisors, and faculty on how to initiate an internship and evaluate interns' work and is a critical resource for leadership preparation programs nationwide and the thousands of school districts that support leadership candidates. Special Features: The National Education Leadership Preparation (NELP) Standards Assessment provides an understanding of the wide breadth of experience and demonstration of skills necessary for school leaders. Self and Superior Assessment helps students to plan according to individual need, experience, goals, and performance expectations. Internship Plans allow students to assess, analyze, and prepare draft individualized internship plans. Professional Report or Portfolio encourages students to evaluate and reflect on their experiences and plan for the future"--